1980
DOI: 10.1159/000232521
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against <i>Aspergillus fumigatus</i>

Abstract: Three different stages were found during growth of Aspergillus fumigatus as characterized by the changes in pH of the medium: (1) An acidic phase (phase I); (2) a second phase (phase II) during which the pH rises till values around pH = 8.5; (3) a third phase (phase III) during which the pH remains constant or drops slightly. During phase I a fast appearance of certain antigenic components was found that is ascribed to an active process of excretion. Additional antigenic components appeared in the culture medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The results indicated that higher carbon source concentrations in the medium (e.g., glucose) result in higher amounts of total nitrogen, soluble proteins, total carbohydrates and soluble carbohydrates in the allergenic extracts [86]. Similar effects were shown in the study by Kauffman et al (1980) [87], where higher glucose concentrations in the medium resulted in higher yields of A. fumigatus mycelium mass [87].…”
Section: Cultivation Mediumsupporting
confidence: 71%
See 3 more Smart Citations
“…The results indicated that higher carbon source concentrations in the medium (e.g., glucose) result in higher amounts of total nitrogen, soluble proteins, total carbohydrates and soluble carbohydrates in the allergenic extracts [86]. Similar effects were shown in the study by Kauffman et al (1980) [87], where higher glucose concentrations in the medium resulted in higher yields of A. fumigatus mycelium mass [87].…”
Section: Cultivation Mediumsupporting
confidence: 71%
“…Different studies have shown that the type of medium (i.e., liquid or solid medium) as well as the medium composition used for fungal cultivation can play an important role for the quality and quantity of fungal raw material obtained for the preparation of fungal extracts [52,78,[83][84][85][86][87][88][89].…”
Section: Cultivation Mediummentioning
confidence: 99%
See 2 more Smart Citations